2011
DOI: 10.1097/scs.0b013e3182077d93
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Growth in Patients With FGFR3Pro250Arg Mutation After Fronto-Orbital Advancement in Infancy

Abstract: The frequency of frontal revision in patients with Muenke syndrome who had FOA in infancy and early childhood is lower than previously reported. Age at forehead advancement inversely correlated with the incidence of relapse and need for secondary frontal procedures. Midfacial retrusion is relatively uncommon in FGFR3Pro250Arg patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Ridgway and colleagues also reported a shorter cranial base than in controls, although they did not report on the status of the spheno-occipital synchondrosis, nor did they hypothesize as to why the cranial base was short. 24 The results of this study also provoke renewed interest in the spheno-occipital synchondrosis as a surgical target in patients with craniosynostosis syndromes. The anatomical region encompassing the spheno-occipital synchondrosis is unforgiving, and surgical mishaps would undoubtedly result in significant patient morbidity and perhaps even mortality.…”
Section: Discussionmentioning
confidence: 93%
“…Ridgway and colleagues also reported a shorter cranial base than in controls, although they did not report on the status of the spheno-occipital synchondrosis, nor did they hypothesize as to why the cranial base was short. 24 The results of this study also provoke renewed interest in the spheno-occipital synchondrosis as a surgical target in patients with craniosynostosis syndromes. The anatomical region encompassing the spheno-occipital synchondrosis is unforgiving, and surgical mishaps would undoubtedly result in significant patient morbidity and perhaps even mortality.…”
Section: Discussionmentioning
confidence: 93%
“…Subsequent magnetic resonance imaging in this patient detected temporal lobe dysgenesis. In a recent study by Ridgway et al [15], 15% of patients (n = 3) demonstrated epilepsy. De Jong et al [14] reported on two Dutch families with Muenke syndrome, including two patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports described several patients with Muenke syndrome and epilepsy [14,15]. Moreover, a 2003 report described early-onset temporal lobe-related epilepsy in a patient with Muenke syndrome associated with temporal lobe dysgenesis, likely contributory to the seizure focus [16].…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies of the corpus callosum have also been reported in patients with Muenke syndrome [1, 36]. Epilepsy has been reported in patients with Muenke syndrome, Saethre–Chotzen syndrome, and Apert syndrome [32, 35, 87, 88]. Patients with Apert syndrome, Pfeiffer syndrome types 2 and 3, or who have neurologic abnormalities, developmental abnormalities, and/or epilepsy should receive a brain imaging study to identify structural anomalies.…”
Section: Managementmentioning
confidence: 99%